2023
DOI: 10.3390/cryst13020325
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Focusing Currents on the Microstructure Evolution and Wear Properties of a Scanning Electron Beam Modified Inconel 625 Nickel Base Alloy Surface

Abstract: The surface of Inconel 625, a nickel-base alloy, was strengthened by vacuum electron beam scanning technology. The evolution of its microstructure was analyzed by electron backscatter diffraction (EBSD) and the friction and wear tester (RETC). The results show that the FCC phase in the microstructure of Inconel 625 nickel-base alloy is stripped and islanded after electron beam scanning treatment. The austenite texture type changes and finally forms a typical cubic texture with a certain strength of S texture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Due to the high integration of Inconel alloys into a large quantity of industrial fields, the possibility of their modification and optimization for specific applications needs to be evaluated. The authors of [20] have studied the microstructure and wear properties of an electron-beam-modified Inconel Ni-based alloy 625, and the results showed that the wear properties were improved due to the strengthening effect of the treatment. However, investigations regarding the effect of treating the surface of Inconel alloys using high-energy fluxes are highly limited regarding the effect of the power of the electron beam on the plasticity of the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high integration of Inconel alloys into a large quantity of industrial fields, the possibility of their modification and optimization for specific applications needs to be evaluated. The authors of [20] have studied the microstructure and wear properties of an electron-beam-modified Inconel Ni-based alloy 625, and the results showed that the wear properties were improved due to the strengthening effect of the treatment. However, investigations regarding the effect of treating the surface of Inconel alloys using high-energy fluxes are highly limited regarding the effect of the power of the electron beam on the plasticity of the specimens.…”
Section: Introductionmentioning
confidence: 99%